If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + 2 = 5m + -3 Reorder the terms: 2 + 8m = 5m + -3 Reorder the terms: 2 + 8m = -3 + 5m Solving 2 + 8m = -3 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 2 + 8m + -5m = -3 + 5m + -5m Combine like terms: 8m + -5m = 3m 2 + 3m = -3 + 5m + -5m Combine like terms: 5m + -5m = 0 2 + 3m = -3 + 0 2 + 3m = -3 Add '-2' to each side of the equation. 2 + -2 + 3m = -3 + -2 Combine like terms: 2 + -2 = 0 0 + 3m = -3 + -2 3m = -3 + -2 Combine like terms: -3 + -2 = -5 3m = -5 Divide each side by '3'. m = -1.666666667 Simplifying m = -1.666666667
| z^2-6z=3 | | z^2+2=3Z | | v^2+8v+16=2v^2+10v+13 | | 3n+8=5n-19 | | 16x-3(4x-7)=6x-(2x+21) | | (7/2v-10)+1=-(4/v-5) | | -(-y)=-13 | | 5x-2=-10 | | 7x+10=3x+2 | | 7y=7(-3) | | (5-8)2-(4-8)2= | | 5p-29=-23+2p | | 3y=12x+4 | | 5t-7=-7+3t | | 20+(-7+2)-(-3-7)= | | 7*(4+7)= | | 2x-5=10+x | | 7X(4+7)= | | 3x-4/2=4x+20 | | 3-7x+3=3 | | (5x/2)-((x-3)/7)=((x+5)/3) | | 29=5+3g | | 5/24x+7/12x^2 | | 5+15x-2=35(x+2) | | 3b-12=32-b | | 20x+5-1=3x-25-8x | | (10+4)+(6-9)-(3-7)= | | 1x+3y+0z=11 | | 16/x-2=8/x | | -3.6x+3.1=3(5.2-1.2) | | y-5=-(7/4)*(x-(-3)) | | 40t=55(t-3) |